Evaluación técnico-financiera a nivel laboratorio de un fluido de perforación de alto desempeño base agua para la perforación de la sección intermedia de un pozo del campo Castilla (2017)
The present work is carried out with the objective of designing a high performance water-based drilling fluid with the capacity to inhibit the reactive lulites present during the drilling of the intermediate section (12 1/4 ") of a well in the Campo Castilla located in the Basin of the Eastern Plains, which, by their hydration, generate tortuous pipe travel and pit instability leading to non-productive times. For its realization it was decided to evaluate the reactivity of 11 rock samples obtained every 500 feet from an initial depth of 2000 feet of the well to study, that reactivity was made by the Suction Time tests Capillary (CST) and Cationic Exchange Capacity (CEC).